2006
DOI: 10.1152/japplphysiol.01453.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α promotes the accumulation of neutrophils and macrophages in skeletal muscle

Abstract: . Pizza. Tumor necrosis factor-␣ promotes the accumulation of neutrophils and macrophages in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 46 publications
4
52
0
3
Order By: Relevance
“…While our present in vivo experiments do not directly determine the cell types contributing to the elevated cytokine production, previous reports have clearly shown that skeletal (Steensberg et al 2000;Keller et al 2001;Frost et al 2002Frost et al , 2003Lang et al 2003) and cardiac muscle (Saito & Papaconstantinou, 2001;Lang et al 2003;Vona-Davis et al 2003) produce numerous cytokines, including TNFα, IL-1β and IL-6, in response to LPS. Further, the modest inflammatory insult and the absence of elevations in TNFα (Peterson et al 2006) support a very limited influx of inflammatory cells into these tissues. Independent of the cell type producing these cytokines, these data show that the inflammatory environment in both skeletal and cardiac muscle can be impacted by short-term vitamin E administration.…”
Section: Discussionmentioning
confidence: 98%
“…While our present in vivo experiments do not directly determine the cell types contributing to the elevated cytokine production, previous reports have clearly shown that skeletal (Steensberg et al 2000;Keller et al 2001;Frost et al 2002Frost et al , 2003Lang et al 2003) and cardiac muscle (Saito & Papaconstantinou, 2001;Lang et al 2003;Vona-Davis et al 2003) produce numerous cytokines, including TNFα, IL-1β and IL-6, in response to LPS. Further, the modest inflammatory insult and the absence of elevations in TNFα (Peterson et al 2006) support a very limited influx of inflammatory cells into these tissues. Independent of the cell type producing these cytokines, these data show that the inflammatory environment in both skeletal and cardiac muscle can be impacted by short-term vitamin E administration.…”
Section: Discussionmentioning
confidence: 98%
“…Following muscle injury, TNF-␣, the chemokines MCP-1, IL-8, and GM-CSF, and COX-2 accelerate muscle repair by recruiting neutrophils and macrophages, reducing the expression of TGF-␤ mRNA, and increasing MyoD mRNA expression (112,113,140,141,161,163). IL-6 does not play an acute role in repairing muscle injury (161), but it is involved in muscle hypertrophy (1,138).…”
Section: Aging Muscle Injury and Inflammationmentioning
confidence: 99%
“…These apparently contradictory findings may be reconciled by differential effects depending on concentration and duration, as stimulation of differentiation was observed in response to low levels of TNF-a, whereas high levels of TNF inhibited regeneration and differentiation in a nuclear factor (NF)-kB-dependent fashion, which involved destabilisation of the myogenic regulatory factor MyoD. Some of the beneficial effects of low levels of TNF-a on regeneration may involve macrophage and neutrophil recruitment, as well as myoblast chemotaxis [22,23].…”
mentioning
confidence: 99%